PENGGUNAAN BAHASA PROKEM TERHADAP EKSISTENSI BAHASA INDONESIA DI KALANGAN MAHASISWA - Saputra, Desma Yuliadi; Andriani, Rina; Astrianingsih, Destri; Pratama, Rizki Nur (Universitas Sultan Ageng Tirtayasa, 2023)
This research was conducted because of the rampant use of prokem language in the Indonesian population, especially among students. This research aims to: 1) to know the form of prokem language used by students, 2) to know the impact of using prokem language in everyday life and 3) to know the effect of using prokem language on the existence of Indonesian language among students. The method used is qualitative descriptive. The data collection techniques used were participant observation techniques and questionnaires. Respondents in this study were prokem students, selected using simple random sampling technique. The results showed: There are 5 forms of prokem language that are often used by students, 2) negative and positive impacts of using prokem language among students in daily communication, 3) the use of prokem language affects the existence of Indonesian language.